Improving Rice Zinc Biofortification Success Rates Through Genetic and Crop Management Approaches in a Changing Environment - Nakandalage, Niluka; Nicolas, Marc; Norton, Robert M.; Hirotsu, Naoki; Milham, Paul J.; Seneweera, Saman (Frontiers in Plant Science, 2016)
Review Article Improving rice zinc biofortification success rates through genetic and crop management approaches in a changing environment Niluka Nakandalage1, Marc Nicolas2, Robert M Norton3, Naoki Hirotsu4, Paul J Milham5 and Saman Seneweera6* 1Faculty of Veterinary & Agricultural Sciences, University of Melbourne, Creswick, VIC 3363, Australia; Email: nnakandalage@student.unimelb.edu.au 2Faculty of Veterinary & Agricultural Sciences, University of Melbourne, Parkville, VIC3010, Australia; Email: marcen@unimelb.edu.au 3International Plant Nutrition Institute, 54 Florence St, Horsham, Victoria, Australia 4Faculty of Life Sciences, Toyo University, 1-1-1 Izumino, Itakura, Gunma 374-0193, Japan; Email: hirotsu@toyo.jp 5Hawkesbury Institute for the Environment, Western Sydney University, LB 1797 Penrith, NSW 2751, Australia; Email: p.milham@westernsydney.edu.au 6Centre for Crop Health, University of Southern Queensland, Toowoomba Qld 4350, Australia; Email: saman.seneweera@usq.edu.au * Correspondence: Saman Seneweera, Centre for Crop Health University of Southern Queensland Toowoomba Qld 4350 Australia Email: saman.seneweera@usq.edu.au Number of words: 5132 Number of figures: 02 Headings and sub headings of paper Abstract 1. Introduction 2. Zinc and human health on a global perspective 3. Rice as source of Zn 4. Key determinents of grain zinc concentration 4.1. Zn uptake and translocation in rice 4.2. Zn remobilization and loading into the grain 4.3. Phytosiderophores in zinc homeostasis 4.4.Plant available Zn in soil 4.5. Rising [CO2] and grain Zn 4.6. Fertilizers as a grain Zn determinant 4.7. Anti-nutrients and Zn bioavailability 5. Ways to overcome global dietary Zn deficiency 6. Conventional breeding as an effective tool for Zn biofortification 7. Conclusions 8. Future research focus Conflicts of Interest Authors and Contributors Acknowledgments References Abstract: Though rice is the predominant source of energy and micronutrients for more than half of the world population, it does not provide enough zinc (Zn) to match human nutritional requirements. Moreover, climate change, particularly rising atmospheric carbon dioxide concentration, reduces the grain Zn concentration. Therefore, rice biofortification has been recognized as a key target to increase the grain Zn concentration to address global Zn malnutrition. Major bottlenecks for Zn biofortification in rice are identified as low Zn uptake, transport and loading into the grain; however, environmental and genetic contributions to grain Zn accumulation in rice have not been fully explored.